A Standardized Telephone Intervention Algorithm Improves the Survival of Ventricular Assist Device Outpatients. Issue 10 (25th May 2018) - Schlöglhofer, Thomas; Horvat, Johann; Moscato, Francesco; Hartner, Zeno; Necid, Georg; Schwingenschlögl, Harald; Riebandt, Julia; Dimitrov, Kamen; Angleitner, Philipp; Wiedemann, Dominik; Laufer, Günther; Zimpfer, Daniel; et al.
Abstract: Ventricular assist devices (VADs) are an established therapeutic option for patients with chronic heart failure. Continuous monitoring of VAD parameters and their adherence to guidelines are crucial to detect problems in an early stage to optimize outcomes. A telephone intervention algorithm for VAD outpatients was developed, clinically implemented and evaluated. During the phone calls, a structured inquiry of pump parameters, alarms, blood pressure, INR, body weight and temperature, exit‐site status and heart failure symptoms was performed and electronically categorized by an algorithm into 5 levels of severity. VAD outpatient outcomes without ( n  = 71) and with bi‐weekly telephone interviews in their usual care ( n  = 25) were conducted using proportional hazard Cox regression, with risk adjustment based on a propensity score model computed from demographics and risk factors. From February 2015 through October 2017, 25 patients ( n  = 3 HeartMate II, n  = 4 HeartMate 3 and n  = 18 HeartWare HVAD) underwent 637 telephone interventions. In 57.5% of the calls no problems were identified, 3.9% were recalled on the next day because of alarms. In 26.5% ( n  = 169), the VAD Coordinator had to refer to the physician due to elevated blood pressure ( n  = 125, >85 mm Hg), INR < 2.0 or > 4.0 ( n  = 24) or edema ( n  = 10), 11.9% of the calls led to a follow‐up because of equipment or exit‐site problems. Propensity‐adjusted 2‐year survival (89% vs. 57%, P  = 0.027) was significantly higher for the telephone intervention group. Continuous, standardized communication with VAD outpatients is important for early detection of upcoming problems and leads to significantly improved survival.